2002
DOI: 10.1038/sj.bjp.0704610
|View full text |Cite
|
Sign up to set email alerts
|

An electrophysiological study of muscarinic and nicotinic receptors of rat paratracheal ganglion neurons and their inhibition by Z‐338

Abstract: 1 To study the mechanisms involved in the action of Z-338, a newly synthesized gastroprokinetic agent, experiments were performed with the paratracheal ganglion cells acutely dissociated from 2-week-old Wistar rats. The e ects of Z-338 on both nicotinic and muscarinic responses of the ganglion cells were studied by nystatin perforated patch recording con®guration under the currentand voltage-clamp conditions. 2 Acetylcholine (ACh) or nicotine, and muscarine or oxotremorine-M (OX-M) induced membrane depolarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
(44 reference statements)
4
6
0
Order By: Relevance
“…It is well documented, however, that Z-338 acts antagonistically on mAChRs (M1 and M2) and nAChRs (Ogishima et al, 2000;Kanemoto et al, 2002), and the present results support this. In addition to the inhibitory action of Z-338 on nAChRs, the present study revealed that Z-338 also inhibits GABA-induced current in a competitive manner in AP neurons.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…It is well documented, however, that Z-338 acts antagonistically on mAChRs (M1 and M2) and nAChRs (Ogishima et al, 2000;Kanemoto et al, 2002), and the present results support this. In addition to the inhibitory action of Z-338 on nAChRs, the present study revealed that Z-338 also inhibits GABA-induced current in a competitive manner in AP neurons.…”
Section: Discussionsupporting
confidence: 78%
“…In the rat paratracheal ganglion, we reported that activation of nAChRs and mAChRs induced inward currents with rapid and slow time courses, and that Z-338 inhibited mAChR-and nAChR-mediated inward currents competitively and uncompetitively, respectively (Kanemoto et al, 2002). AP neurons are considered to possess nAChRs but not mAChRs (Strominger et al, 2001), and in the present experiments Z-338 inhibited nicotine-induced inward currents as in the case of paratracheal ganglion cells.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…According to the previous report, mecamylamine (10 Ϫ8 ϳ10 Ϫ4 M) inhibits nicotine-induced current with an IC 50 of 1.7 ϫ 10 Ϫ6 M in dissociated PTG neurons (Kanemoto et al 2002), and the currents are fully blocked by mecamylamine at a concentration larger than 10 Ϫ4 M. In addition, 50 M mecamylamine reduced cholinergic EPSC amplitudes by 33% in central nicotinic receptors (Chu et al 2000), and 10ϳ20 M mecamylamine blocked 62-79% of the EPSC in other ganglionic nicotinic receptors (Nong et al 1999). Thus the inhibitions by mecamylamine on EPSCs and nicotine-induced currents are comparative.…”
Section: Discussionmentioning
confidence: 83%